The quality of life of postmenopausal women with hip and knee advanced dysfunction due to osteoarthritis prior to joint replacement - Morawik, Iwona; Jurewicz, Alina; Jędrych, Marian; Jabłoński, Mirosław (Polish Journal of Public Health, 2012)
Introduction. Surgical replacement of hip and knee joints with advanced degenerative and deformative changes is a method commonly used for treatment of such important and frequent ailments of the locomotor organ. In accordance with an obligatory system of scheduling in Poland the waiting time for a hip or knee endoprothesoplasty takes up to two years. Aim. The aim of the research was to characterize and assess the quality of life of postmenopausal patients with the degenerative changes of hip joints (coxsarthrosis) and knee joints (gonarthrosis) waiting for joint arthroplasty. Material and methods. The research was based on two groups of postmenopausal women aged 50-62 with advanced osteoarthritis of the hip (n=59) and knee (n=51). The quality of life just prior to the planned surgery was measured by means of an individually prepared survey where two questions from the HRQ Johansson and co. survey (1992) were used. In the statistical analysis with the significance of p<0.05 statistical hypotheses were verified with the use of U Mann-Whitney non-parametric test and Chi2 Pearson’s test as well as Fisher’s exact test. Results. Advanced degenerative osteoarthritis of the knee more frequently than of the hip was related to overweight or obesity (p=0.02). In contrast to gonarthrosis, degenerative hip disease more often made foot care difficult (p=0.0002). The state of mind and individual health-esteem of patients with coxarthrosis compared with the same period a year before was significantly lower than of the patients with gonarthrosis (p=0.05). Due to lengthy time of symptoms the patients with hip dysfunction decided on operation faster (p<0.0001). Gonarthrosis occurred more frequently in a city, while patients from rural environment were more susceptible to hip diseases (p=0.04). Advanced coxarthrosis more often than gonarthrosis was related in investigated groups of postmenopausal females to elementary and vocational education rather than higher and post-vocational (p=0.05). Conclusions. Coxarthrosis demands more rapid surgery than gonarthosis in comparable postmenopausal women. Coexistence of overweight and obesity related to gonarthrosis indicates a possibility, need and full medical justification for a body mass reduction in these very patients.